Contemporary Issues and Practicalities in Completing Advance Care Planning for Patients With Severe COPD Living Alone: A Qualitative Study. Issue 1 (2nd January 2022) - Hirakawa, Yoshihisa; Aita, Kaoruko; Nishikawa, Mitsunori; Arai, Hidenori; Miura, Hisayuki
Abstract: Health care professionals working with older people living alone with chronic obstructive pulmonary disease (COPD) to complete advance care planning (ACP) often encounter the double burden of social isolation and acute exacerbations in this planning. The study explored clinicians' perceptions regarding factors influencing the completion of ACP for older people with COPD living alone. Individual interviews were conducted with 18 health care professionals using the video meeting platform in 2020. A semi-structured interview guide included: (a) behavior and lifestyle related to decision-making, (b) desired place to die, and (c) facilitators and barriers to autonomy in patients with severe COPD who live alone. Five main themes were identified: information sharing among team members, patient readiness, desired place of death, economic constraints, and care at the time of and after death. Partly due to the heterogeneity and complexity of clinical courses and treatment responses of COPD, a wide range of social issues of a person's life were related to practicality in the completion of ACP for older people with COPD living alone. Social work knowledge and skills such as in-depth interviewing, outreach finance and welfare support, and holistic perspective play an essential role in completing ACP for COPD patients living alone.